Digital drugs:between theScientific Truth and the Legal View - Lebsir, Fatima; Labiod, Lynda (Milev Journal of Research and Studies, 2021)
The purpose of the study is to uncover the digital drugs essence as a new and dangerous concept of unregulated addiction, which has emerged during the ever increasing use of modern informatics and communication technologies, as a new source of digital abuse that equates or exceeds the dangerous effects of traditional drugs on the human body. Given the digital harm that took over our societies, and lurks our youth and children, in the absence of explicit legal texts criminalizing it. Through this paper, we attempt to deconstruct the concept of digital drugs, the motives that lay behind its use, its effects, the reality of its existence, then the law's view towards this type of abuse.